FRI0168 Etanercept serum trough levels are correlated with clinical activity in rheumatoid arthritis patients with long-term treatment with etanercept. (23rd January 2014) - Plasencia, C.; Pascual-Salcedo, D.; Alcozer, P.; Garcia-Carazo, S.; Franco, K. N.; Cajigas, D.; Bonilla, G.; Lojo, L.; Nuño, L.; Villalba, A.; Peiteado, D.; Arribas, F.; et al.
Abstract : Background: The use of anti-TNF therapy, as Etanercept (Etn), has proven to be effective in patients with rheumatoid arthritis (RA). However, a significant proportion of patients develop clinical inefficacy or adverse effects, resulting in treatment interruption. Recently, it has been reported that Etn serum trough levels are correlated with clinical activity in RA patients, so that, patients with low Eta serum trough levels had a worse clinical response. Objectives: To evaluate whether Etn serum trough levels correlate with clinical activity and treatment discontinuation in RA patients treated with Etn. Methods: In this ambispective study, 44 RA patients treated with Etn were included. Clinical activity was assessed using the Disease Activity Score 28 (DAS28), clinical improvement by the delta-DAS28 and response to treatment using EULAR criteria at baseline and at 1st, 2nd and > 3rd years of treatment. In every patient Etn was administered subcutaneously at a dose of 50 mg/week and Eta levels were assessed every 6 months by capture ELISA. Blood samples were obtained up to 24 hours before administration of Etn. Statistical analysis was performed using SPSS 11.0. For the statistical study, serum trough levels were divided into low levels (LL<1000 ng/ml) and high (HL ≥ 1000 ng/ml). Results: Of the 44 RA patients treated with Etn, 34 (77.2%) were women. The mean age was 60.2 ± 12.7 years and the mean disease duration was 16.1 ± 9.9 years. The baseline clinical activity (DAS28) was 4.9 ± 1.0 and there were no differences between patients who later developed Etn LL and HL (5.3 ± 1.5 with LL vs 4.9 ± 0.8 with HL, p = 0.287). Clinical activity (DAS28) was higher in patients with Etn LL at all studied time points (4.3 ± 0.9 with LL vs 2.6 ± 0.6 with HL at 1st year, p = 0.003; 4.3 ± 1.2 with LL vs 2.5 ± 0.7 with HL at 2nd year, p = 0.002; 4.5 ± 0.9 with LL vs 2.7 ± 0.6 with HL at > 3rd year; p = 0.000). Clinical improvement (delta-DAS28) was lower in patients with Etn LL throughout the study (-0.7 ± 1.1 with LL vs 2.1 ± 0.9 with HL at 1 year, p = 0.006; 0.8 ± 2.1 with LL vs 2.4 ± 0.9 with HL at 2nd year, p = 0.036; 0.86 ± 1.4 with LL vs 2.2 ± 0.9 with HL at > 3rd year, p = 0.003). The drop-out of biological therapy during the study was more frequent in patients with Etn LL [7/13 (53.8%) vs 1/31 (3.2%) with HL, p = 0.000]. Etn serum trough levels (Mdn, P25-P75) were higher in patients with EULAR good (GR) and moderate response (MR) than in non-responders (NR) patients [2287.0; 1488.7-2625.0 classified as GR vs 821.5; 500.0-1143.0 with MR vs. 16.0; 16.0-16.0 with NR at 1st year, p = 0.026; 1379.2; 1190.5-3347.0 with GR vs 2225.0; 2225.0-2225.0 with MR vs 352.0; 0.0-973.0 with NR at 2nd year, p=0.154; 2300.0; 1812.0-3312.0 with GR vs 1274.0; 700.5-2605.0 with MR vs 37.0; 15.0-1200.0 with NR at >3rd year, p=0.007]. Conclusions: The presence of low Etn serum trough levels correlates with a poor clinical response to Etn and a higher frequency of treatment discontinuation. However, patients classified as responders have higher Etn serum trough levels and a low frequency of treatment discontinuation. Disclosure of Interest: None Declared